Endothelial thymosin beta 4 acts during vascular development to facilitate mural cell recruitment to the vessel wall. (22nd September 2015) - Rossdeutsch, A; Smart, N; Turner, M; Riley, PR
Abstract : Introduction: Thymosin β4 (Tβ4) is an endogenously occurring 43-amino acid peptide demonstrated to have cardioprotective properties in the setting of acute myocardial infarction. 1 During embryogenesis, Tβ4 is secreted by the myocardium and stimulates epicardial progenitor cell invasion of the myocardium in order to form the coronary vasculature. 2 In order to gain further insight into this process, we examined whether Tβ4 plays a role in the development of the systemic vasculature. Results and Methods: In situ hybridisation studies revealed expression of Tβ4 in the developing murine vasculature from E9.5 onwards. Immunofluorescence demonstrated that this vascular expression of Tβ4 is localised to the endothelial cell lineage. We initially used a Tβ4 knockout mouse to assess the effect of global loss of Tβ4 function on vascular development. We observed that a proportion of Tβ4 null embryos displayed pericardial and coelomic cavity haemorrhage at E10.5 (fig 1 ). This phenotype is caused by reduced mural cell recruitment to the dorsal aorta in Tβ4 null mice (fig 2 ). In order to understand further the mechanism through which Tβ4 acts, we knocked down Tβ4 specifically in the endothelial cell lineage by crossing conditional Tβ4 shRNA mice 2 with Tie2-Cre-expressing mice. We observed that the phenotype present in the global knockout model could be recapitulated in this system. This confirms that the phenotypes seen are due to a primary role of Tβ4 function in the developing endothelium and are not secondary to defects in other embryonic lineages. Conclusions: These findings lead us to propose a model whereby Tβ4 acts as an endothelial secreted paracrine factor necessary for one or more of the differentiation, migration or proliferation of mural cell progenitors during vascular development and the formation of a stable blood vessel. This discovery may have implications for adult cardiovascular diseases in which aberrant endothelial–mural cell interactions play a pathological role, such as in coronary restenosis.